Implementasi Model Soil dan Water Assessment Tool (SWAT) Dalam Pengelolaan Das Mikro Sei Tanduk - Nurdin Nurdin; Imam Suprayogi; Muhammad Shalahuddin; Ermiyati Ermiyati; Siswanto Siswanto; Andre Novan (Dinamika Lingkungan Indonesia, 2023)
The Soil and Water Assessment Tool (SWAT) model which is integrated with the Geographic Information System (GIS) can provide an overview or prediction of the influence of land management on the hydrology of the Micro Sei Tanduk watershed in accordance with the interests of evaluating and monitoring watershed management activities. The purpose of this study was to analyze the management of the Sei Tanduk Micro watershed based on land use patterns, as a basis for determining the best recommendations for planning and evaluating the Indragiri Rokan Watershed Management Project Activities for Fiscal Year 2003 by compiling a Master Plan for the Micro Sei Tanduk Watershed Master Plan Rumbio Village, Kampar Regency. The research method is to process primary and secondary data using a SWAT model that is integrated with GIS in analyzing hydrological characteristics in land use scenarios in the management of the Micro Sei Tanduk watershed, as a basis for providing recommendations. The best recommendation from the evaluation and analysis of the Micro Sei Tanduk watershed management based on land use patterns is scenario 2 in the form of applying agroforestry on mixed dry land agriculture with the insertion of forestry trees based on community participation in the Micro Sei Tanduk watershed, Rubio Village, Kampar District, Kampar Regency.